Molecular differences in IDH wildtype glioblastoma according to MGMT promoter methylation. Issue 3 (24th August 2017) - Kessler, Tobias; Sahm, Felix; Sadik, Ahmed; Stichel, Damian; Hertenstein, Anne; Reifenberger, Guido; Zacher, Angela; Sabel, Michael; Tabatabai, Ghazaleh; Steinbach, Joachim; Sure, Ulrich; Krex, Dietmar; et al.
Abstract: Background: O 6 -methylguanine-DNA-methyltransferase ( MGMT ) promoter methylation status is a predictive biomarker in glioblastoma. We investigated whether this marker furthermore defines a molecularly distinct tumor subtype with clinically different outcome. Methods: We analyzed copy number variation (CNV) and methylation profiles of 1095 primary and 92 progressive isocitrate dehydrogenase wildtype glioblastomas, including paired samples from 49 patients. DNA mutation data from 182 glioblastoma samples of The Cancer Genome Atlas (TCGA) and RNA expression from 107 TCGA and 55 Chinese Glioma Genome Atlas samples were analyzed. Results: Among untreated glioblastomas, MGMT promoter methylated ( mMGMT ) and unmethylated ( uMGMT ) tumors did not show different CNV or specific gene mutations, but a higher mutation count in mMGMT tumors. We identified 3 methylation clusters. Cluster 1 showed the highest average methylation and was enriched for mMGMT tumors. Seventeen genes including gastrulation brain homeobox 2 ( GBX2 ) were found to be hypermethylated and downregulated on the mRNA level in mMGMT tumors. In progressive glioblastomas, platelet derived growth factor receptor alpha ( PDGFRA ) and GLI2 amplifications were enriched in mMGMT tumors. Methylated MGMT tumors gain PDGFRA amplification of PDGFRA, whereas uMGMT tumors with amplified PDGFRA frequently lose this amplification upon progression. Glioblastoma patients surviving <6 months and with mMGMT harbored less frequent epidermal growth factor receptor ( EGFR ) amplifications, more frequent TP53 mutations, and a higher tumor necrosis factor–nuclear factor-kappaB (TNF-NFκB) pathway activation compared with patients surviving >12 months. Conclusions: MGMT promoter methylation status does not define a molecularly distinct glioblastoma subpopulation among untreated tumors. Progressive mMGMT glioblastomas and mMGMT tumors of patients with short survival tend to have more unfavorable molecular profiles.